Examining the Marketing Effectiveness of Sports Team Sponsorship on Consumer Behaviour: A Cross-Cultural Comparison between Low and High Context Cultures - Nasser AlShawaaf (Universitas Majalengka, 2023)
Sports sponsorship is a marketing activity that requires huge budget where companies seek to achieve business objectives. The study compares between low and high context cultures to understand the effect of football team sponsorship on consumer behaviour. An online survey was conducted through Qualtrics with 380 responses. Results show that culture affects the outcome of football team sponsorship on brand image, purchase intention, and brand loyalty. Football team sponsorship leads to higher marketing effectiveness in low context culture. Low context culture has either the same outcome of high context culture or better and vice versa. High context culture tends to have some negative attitudes toward the brands that are sponsoring football teams. It is recommended for marketers to allocate football team sponsorship budget to low context culture for better outcome. Future work should aim to compare cultural effect on sports sponsorship in other sports such as basketball, tennis, golf … etc.